Beneficial modulation of human health in the oral cavity and beyond using bacteriocin-like inhibitory substance-producing streptococcal probiotics - Tagg, John R.; Harold, Liam K.; Jain, Rohit; Hale, John D. F. (Frontiers in Microbiology, 2023)
The human oral cavity contains a diversity of microbial habitats that have been adopted and adapted to as homeland by an amazingly heterogeneous population of microorganisms collectively referred to as the oral microbiota. These microbes generally co-habit in harmonious homeostasis. However, under conditions of imposed stress, as with changes to the host’s physiology or nutritional status, or as a response to foreign microbial or antimicrobial incursions, some components of the oral “microbiome” (viz. the in situ microbiota) may enter a dysbiotic state. This microbiome dysbiosis can manifest in a variety of guises including streptococcal sore throats, dental caries, oral thrush, halitosis and periodontal disease. Most of the strategies currently available for the management or treatment of microbial diseases of the oral cavity focus on the repetitive “broad sweep” and short-term culling of oral microbe populations, hopefully including the perceived principal pathogens. Both physical and chemical techniques are used. However, the application of more focused approaches to the harnessing or elimination of key oral cavity pathogens is now feasible through the use of probiotic strains that are naturally adapted for oral cavity colonization and also are equipped to produce anti-competitor molecules such as the bacteriocins and bacteriocin-like inhibitory substances (viz BLIS). Some of these probiotics are capable of suppressing the proliferation of a variety of recognized microbial pathogens of the human mouth, thereby assisting with the restoration of oral microbiome homeostasis. BLIS K12 and BLIS M18, the progenitors of the BLIS-producing oral probiotics, are members of the human oral cavity commensal species Streptococcus salivarius. More recently however, a number of other streptococcal and some non-streptococcal candidate oral probiotics have also been promoted. What is becoming increasingly apparent is that the future for oral probiotic applications will probably extend well beyond the attempted limitation of the direct pathological consequences of oral microbiome dysbiosis to also encompass a plethora of systemic diseases and disorders of the human host. The background to and the evolving prospects for the beneficial modulation of the oral microbiome via the application of BLIS-producing S. salivarius probiotics comprises the principal focus of the present review.